Violência ou martírio? uma análise da violência e do significado do martírio nas fontes e interpretações islâmicas - Camargo, Valéria (2012)
The terrible suicide terrorist attacks the so called human bombs - generally associated to Muslim radical groups have been submitted to misunderstood interpretations. Anti-Islamic authors impute this actions to Islam as a whole, as being consequence of a concept of jihad understood as a holy war , or a conflict of civilizations that Muslim carry on in order to overcome the enemies of Islamic faith and culture. On the other hand, radical groups consider these actions as a political defense of Islam or as an altruistic suicide and a kind of martyrdom for Allâh´s cause. In face of these interpretations, the thesis aims to point out a new view by going deep into the Islamic sources, namely Koran and Ahadith. First, an explanation is made about Islamic sources. The most important texts on the subject have been collected according to some key words, by following the hypothesis that the true meaning of jihad is not an aggressive and violent action. Jihad must be understood in a wild sense of practicing virtues, love and social justice. So, suicide terrorism is never altruistic but a real suicide; not a martyrdom but an anti-social behavior that is definitively condemned by Koran and Ahadith. In order to emphasize this position, the thesis points out the spiritual and mystic aspects of Islamic faith and its social solidarity. It also rejects the interpretations and generalizations of anti-Islamic writers who impute to Islam the responsibility and the strategic logic of the suicide terrorism